A systemic approach to processes of power in learning organizations: Part II – triple loop learning and a facilitative intervention in the "500 schools project". Issue 5 (2nd October 2018) - Flood, Robert L.; Romm, Norma R.A.
Abstract : Purpose: The purpose of this paper is to give practical insights into the systemic approach to organizational learning "triple loop learning" (TLL; introduced in Part I) by reflecting on a facilitated research-and-intervention undertaken in South Africa as part of the "500 Schools Project". Design/methodology/approach: The authors reflect on one of the many researcher-assisted interventions in the "500 Schools Project" by retrospectively reflecting on the case through the principles of TLL. Findings: The authors show that researcher-assisted intervention can be genuinely transformative given two conditions: The principles of TLL are embraced, and researchers are committed to such principles and passionate about social transformation. In particular, the case study illustrates how we might address processes of power in processes of design and in processes of debate. The focus on power arguably helped to shift "power over" (power as domination) to "power to" enact empowering designs, "power to" co-develop responsible decision-making and "power to" transform relations with each other and with life on Earth. Originality/value: The authors introduce an original approach to TLL that directly addresses issues relating to processes of power. The value of the TLL is that it encourages researchers, learning facilitators and practitioners of the learning organization to engage with processes of power without neglecting other important organizational and environmental issues.